Factores determinantes de la informalidad y su efecto en las utilidades de los comerciantes del pasaje paquito Iquitos año 2022 - Vasquez Davila, Jhonatan (2024)
The present research aimed to determine the relationship between the factors of informality and the profits of the merchants of Pasaje Paquito, Iquitos in the year 2022. For this, an applied methodology and non-experimental design were used. For data collection, it was carried out through the survey and the collection of information, applying as an instrument the questionnaire and a registration form. For this research, it was concluded that the determinants of informality with the highest percentages are compliance with all the requirements to be formal (49%), tax penalties that sometimes affect income and a formalization process that sometimes takes time. In addition, there is a high level of profit among merchants (30%), partly because they manage to achieve their sales goals almost always, although sometimes the sale of products generates daily expenses that they must cover. Finally, accounting costs and bureaucratic barriers have a significant impact on profit, with a correlation of 0.433 and 0.357 respectively, demonstrating a dependence on the utility of these factors. However, compliance with legality has no discernible effect on utility.